Advancing Poland in Exile: World War II Intellectuals in North America - Pula, James S. (Polonia Inter Gentes, 2023)
The outbreak of World War II left thousands of Polish citizens unable to safely return to their homeland, among them scholars who were quick to form a “Polish University in Exile” in Paris as a means of ensuring wartime continuity in their respective fields, followed by an Association of Polish University Professors and Lecturers in London after the fall of France. The cadre of intellectuals and artists who were in the United States in 1939 were joined during and in the immediate aftermath of the war by hundreds of others. This article chronicles the efforts of these academics to not only support the political and military goals of the Polish government-in-exile, but especially their creation of valuable, enduring organizations in North America that preserved priceless archival materials, published important monographs and journals, and greatly broadened the North American footprint of Polish studies among both Polish and non-Polish scholars in all their diverse disciplines.